PENGEMBANGAN BAHAN AJAR TEKNIK PEMESINAN FRAIS UNTUK SISWA KELAS XI JURUSAN TEKNIK PEMESINAN DI SMK MUHAMMADIYAH PRAMBANAN - Wachid Nur Ramadhan; Setuju Setuju (Jurnal Taman Vokasi, 2016)
Passivity of students in learning, together with limited productive lesson teaching materials particularly in milling machine techniques, lead to a low level understanding of students in particular subjects. Development of teaching materials in the form of module is expected to be the solution of existing learning problems. This study is purposed to determine the development of teaching materials in the form of milling machine techniques modules and measure the quality of the feasibility of such modules through an assessment by experts and students. Thirty two students of 12th grade at Machine Engineering Department of SMK Muhammadiyah Prambanan were involved as the object of this study. The development model used in this study is analysis, design, development and implementation. Data analysis techniques used in the form of descriptiveÂ  analysis. The results of this study are the development of teaching materials in the form of 4 stages modules (analysis, design, development and implementation). Expertsâ€™ assessment shows that this module is qualified and appropriate to be used in learning process. While the assessment by 32 students known that the average score in graphic, content and language is 21.28 with quality category of "very good", 41,50 with quality category of "good", 21.12 with quality category "very good". A total of 53.12% of students expressed that module quality is "good". From the data, it can be concluded that the module of teaching materials development in milling machine techniques is "good" so that it is appropriate in learning process at SMK MuhammadiyahPrambanan.